2022
DOI: 10.1007/s12639-022-01556-5
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis and symptoms severity in patients with COVID-19 in referral centers in Northern Iran

Abstract: Toxoplasmosis has been categorized as one of the long-lasting protozoan parasitic infections. It affects almost one-third of the world’s population. In recent years, several documented studies have elucidated that infected individuals have a remarkably higher incidence of distinct health problems and show various adverse effects. In the PCR-positive COVID-19 patients in Gonbad-e-Kavus, Kalaleh, and Minoodasht counties in the northern part of Iran from June 2021 to December 2021, we sought to investigate any po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Furthermore, the prevalence of anti- T. gondii IgM and IgG antibodies were 5.0% and 26.1%, respectively, in COVID-19 patients. However, no significant associations have been found between T. gondii infection and COVID-19 severity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prevalence of anti- T. gondii IgM and IgG antibodies were 5.0% and 26.1%, respectively, in COVID-19 patients. However, no significant associations have been found between T. gondii infection and COVID-19 severity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…They reported no link between latent toxoplasmosis and COVID-19 severity, although a high rate of toxoplasmosis was noticed in different COVID-19 severity categories [ 19 , 30 ]. A third study was also done in Iran and concluded that neither acute nor latent toxoplasmosis are risk factors for COVID-19 [ 31 ]. Similarities between the immune response against both SARS-CoV-2 and Toxoplasma are suggested to abolish the influence of toxoplasmosis on COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to Geraili et al 13 , who found that the seroprevalence (IgG) of T. gondii among COVID-19 positive cases was 26.1%, at a marginal error of 0.05, the power of the study was 95%, the estimated sample size was a minimum number of 296 and after addition 10% (30 cases) for any suspected defect in the patient's records or lab analysis. The final minimal sample was 326 COVID-positive cases.…”
Section: Methodsmentioning
confidence: 99%